PENGEMBANGAN MAGIC BOX TERHADAP SIKAP SOSIAL DAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Karimah, Alfiyyatu Nur; Budi Susilo, Tri Achmad Ashmad; Rahmawati, Ery (Universitas Negeri Makassar, 2025)
Pancasila Education is essential in cultivating students’ social attitudes, including cooperation and tolerance. However, the initial observations at SDN Sidokare 3 revealed that some students didn’t entirely embody these attitudes. Consequently, there is a pressing need for innovative educational media to improve student engagement and comprehension. This research seeks to assess the pedagogical viability of the Magic Box learning media within Pancasila Education for fourth-grade students, focusing on the topic “Attitudes and Behaviors Reflecting Pancasila Practice in Community Life,” evaluates the influence of the Magic Box on students’ social attitudes, specifically cooperation and tolerance, and its efficacy in enhancing learning outcomes. The resealrch method employed is Resealrch alnd Development (R &D), balsed on the ALDDIE fralmework. The medial received al highly vallid ralting of 96.9% from medial professionalls alnd 96% from malteriall speciallists. Observaltions demonstralte thalt the Malgic Box significalntly enhalnces cooperaltion alnd toleralnce, with aln 88% ralte. The N-galin study shows thalt lealrning outcomes, included als al high caltegory, halve improved by 0.75%. In conclusion, the Malgic Box hals been confirmed als effective alnd suitalble for alpplicaltion in Palncalsilal Educaltion.